2012
DOI: 10.1073/pnas.1213169109
|View full text |Cite
|
Sign up to set email alerts
|

Counting primary loops in polymer gels

Abstract: Much of our fundamental knowledge related to polymer networks is built on an assumption of ideal end-linked network structure. Real networks invariably possess topological imperfections that negatively affect mechanical properties; modifications of classical network theories have been developed to account for these defects. Despite decades of effort, there are no known experimental protocols for precise quantification of even the simplest topological network imperfections: primary loops. Here we present a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
225
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 198 publications
(238 citation statements)
references
References 44 publications
8
225
1
4
Order By: Relevance
“…Experimental techniques such as rheology/spectroscopy and multiple-quantum NMR can provide semi-quantitative information related to the loop structure [31][32][33]. Recently, Zhou et al reported 'network disassembly spectrometry' (NDS), which is the first experimental method for directly quantifying primary loops [34,35]. Theory that can fully describe the dilution and chain-length effects on primary loop fraction observed in experiments is lacking.…”
mentioning
confidence: 99%
“…Experimental techniques such as rheology/spectroscopy and multiple-quantum NMR can provide semi-quantitative information related to the loop structure [31][32][33]. Recently, Zhou et al reported 'network disassembly spectrometry' (NDS), which is the first experimental method for directly quantifying primary loops [34,35]. Theory that can fully describe the dilution and chain-length effects on primary loop fraction observed in experiments is lacking.…”
mentioning
confidence: 99%
“…The experimental storage modulus (∌0.3 kPa) is much lower than the predicted value, suggesting incomplete cross-linking or the formation of elastically ineffective loops. Loop formation would be expected to be enhanced by the fact that the network precursors AAA and BB were mixed at millimolar concentrations; for example, Zhou et al (21) showed that loop fractions approach 80% in networks formed from telechelic polyethylene glycol oligomers at concentrations of ∌5 mM. In addition, the excluded volume of the ELP domain may slow the binding of SpyCatcher to internal SpyTag sites (13), and favor chain extension at the expense of cross-linking.…”
mentioning
confidence: 99%
“…196 For PEG segments with a degree of polymerization of $15, 194 each PEG arm contributes a length of approximately 3 nm to the overall polymer chain. 197 Therefore, a change in chain length from $11 to $7.5 nm upon ligand binding is anticipated. This 32% decrease in chain length would result in a 69% reduction in gel volume for isotropic deswelling, consistent with the volume decrease observed for the largest swelling levels.…”
Section: Hydrogels With Biological Recognition Propertiesmentioning
confidence: 99%